Hypogonadotropic Hypogonadism in Non-Functioning Pituitary Adenomas: Impact of Intervention - Monteiro, Diana Margarida; Freitas, Paula; Vieira, Romana; Carvalho, Davide (Experimental and Clinical Endocrinology & Diabetes, 2017)
To determine the prevalence of hypogonadotropic hypogonadism (HH) among patients with non-functioning pituitary adenomas (NFPA) and the post-surgery outcome on pituitary gonadotropins secretion (PGS); to determine the prevalence of erectile dysfunction (ED) on male patients with NFPA, to evaluate the impact of testosterone replacement therapy (TRT) in those with HH. Retrospective evaluation of gonadal function in 109 NFPA patients (45 males), with a mean age of 51.8 years, diagnosed on the last 10 years. ED questionnaire applied to 34 male patients. Male patients with NFPA were significantly older (males 58.1±15.8 vs. females 47.4±16.94; p=0.001). Most patients had macroadenomas (67%; p=0.001) and only a minority were incidentalomas (19%; p<0.001). Prevalence of HH was 40% (60% on males, 25% on females; p<0.001). Surgery was performed in 54% of all patients (71% of males, 42% of females; p<0.003). After intervention, 14% became HH, 69% maintained previous function and 17% improved. On the questionnaire, 76% reported having ED, 54% of which had HH and 21% were under TRT. Of the patients under TRT, 79% still had ED. Median age of patients with ED was significantly higher [with ED 65 vs. without 49 years; p=0.012). There was no BMI difference between patients with or without TRT (28.0 vs. 27.4 Kg/m2). NFPA was more frequent in older rather than younger patients. Males were older, had more HH and surgery. There was no significant improvement of pituitary function with surgery (17%) and 13% became iatrogenic HH. TRT had a low efficacy to improve ED in these patients.
Keywords: erectile dysfunction; testosterone replacement therapy; hypogonadotropic hypogonadism; surgery; pituitary adenoma; non-functioning